Tantangan Pembiayaan Murabahah Konsumtif pada Bank Syariah Indonesia - Saputra, Reza Eka; Arsyad, Kamaruddin; Possumah, Bayu Taufiq; Majid, Jamaluddin; Wawo, Andi (Tangible Journal, 2025)
This study aims to analyze the challenges of consumptive murabahah financing contracts in Islamic Banks in Indonesia. Using a qualitative library research approach, the study relies on secondary data collected through Google Scholar searches supported by the Publish or Perish (PoP) software with the keyword “Murabahah Financing in Islamic Banks in Indonesia 2020–2025.” Only journal articles were used as data sources. From 29 relevant references, seven specifically examined Bank Syariah Indonesia (BSI). All collected data were compiled, analyzed, and interpreted to formulate a literature-based conclusion. The findings reveal that murabahah is the most dominant consumptive financing product at BSI in terms of user interest and transaction volume. Its popularity is driven by its simplicity, margin certainty, and lower risk of default. In practice, murabahah bil wakalah is widely implemented, creating an impression similar to conventional credit schemes. Although BSI’s implementation complies with PSAK 102 and DSN–MUI fatwas, several challenges remain, particularly customers’ limited understanding of contract mechanisms, lack of transparency in margin determination, and the potential financial burden borne by customers.